Attitudes of police officers toward offenders: implications for future training - Cunha, Olga Cecília Soares (2017)
Purpose Police officers’ attitudes toward criminals are critical to the justice system’s response to crime. The purpose of this paper is to investigate the attitudes toward offenders (ATOs) among police officers.Design/methodology/approach To assess police officers ATOs, the authors adapted the Attitudes Toward Prisoner scale to produce the ATO scale. The scale was completed by 431 male police officers in a Portuguese police institution.Findings The results revealed that police officers hold more negative ATOs than correctional officers and graduate students. Moreover, the results revealed significant differences in average ATO scores according to police officers’ age, years of service, marital status and education; namely, police officers who were older, married, less educated, and with more years of police service had more positive ATOs. However, the results revealed that these demographic factors had a limited value in predicting attitudes, as none of them emerged as a predictor of ATOs.Originality/value Nonetheless, considering the relevance of attitudes in law enforcement procedures, the implications for training police officers are provided, specifically using critical incident technique strategies.